A Possible Potentiating Antidepressant Effect of Venlafaxine by Recombinant Rat Leptin in a Rat Model of Chronic Mild Stress - Kamal, Sahar Mohamed (International Journal of Biotechnology for Wellness Industries, 2013)
The present study was designed to investigate the possible changes in forced swimming test (FST), prefrontal cortical glutamate and gamma amino-butyric acid (GABA) contents by leptin and/or venlafaxine in chronic mild stress (CMS)-induced anhedonia in male albino rats. They were divided into 5 groups: the first group was not exposed to CMS, the second group received normal saline with exposure to CMS, the third group received leptin 1 mg/kg/day intraperitoneally (ip) for 3 weeks after CMS induced anhedonia was assesed by sucrose consumption test, the fourth group received venlafaxine 8 mg/kg/day ip for 3 weeks after CMS protocol, and the fifth group was received both medications for 3 weeks. Leptin and/or venlafaxine restored the changes in sucrose consumption test, behavioural assessment by forced swimming test (FST) as well as prefrontal cortical GABA and glutamate contents in the control stressed group. Furthermore, combination of both treatments seems to be more efficacious than venlafaxine alone in these parameters. In conclusion,these results showed a potential antidepressant role of leptin and beneficial therapeutic interaction with venlafaxine by affecting the GABA and glutamate level in prefrontal cortex. These actions could make leptin a potentially valuable drug for the treatment of depression.